1989
DOI: 10.1159/000234732
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eicosapentaenoic Acid Rich Menhaden Oil and MaxEPA on the Autoimmune Disease of Mrl/l Mice

Abstract: The Mrl lpr/lpr (Mrl/l) mouse is a model for systemic lupus erythematosus and rheumatoid arthritis in humans. The diet of Mrl/l mice was supplemented with EPA (see Introduction) in menhaden oil or in the commerical fish oil MaxEPA. The survival of mice was not affected by the dietary manipulations. The addition of menhaden oil decreased the severity of the renal pathology. However, MaxEPA containing the same amount of eicosapentaenoic acid was considerably less effective. A diet deficient in polyunsaturated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2025
2025

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Moreover, a recent study reported that omega-6 PUFAs did not have the same beneficial effect on lupus nephritis as omega-3 PUFAs ( 96 ). The disease-ameliorating effect of omega-3 PUFA against murine lupus was further confirmed in several lupus-prone mouse models other than NZB/W F1 ( 86 , 97 , 98 ). Starting late 1980s, more than 10 interventional studies with omega-3 PUFAs as treatments have been done in patients with SLE.…”
Section: Environmental Factors and Slementioning
confidence: 76%
“…Moreover, a recent study reported that omega-6 PUFAs did not have the same beneficial effect on lupus nephritis as omega-3 PUFAs ( 96 ). The disease-ameliorating effect of omega-3 PUFA against murine lupus was further confirmed in several lupus-prone mouse models other than NZB/W F1 ( 86 , 97 , 98 ). Starting late 1980s, more than 10 interventional studies with omega-3 PUFAs as treatments have been done in patients with SLE.…”
Section: Environmental Factors and Slementioning
confidence: 76%
“…Elegant studies from the Fernandes laboratory have related the delayed onset and decreased severity of renal disease exhibited in fish oil-fed NZBWF1 mice to reduced IL-1β, TNF-α, TGFβ1, ICAM-1 and fibronectin expression and increased expression of antioxidant enzymes [16], [17], [18], [19], [20]. The ameliorative effects of n-3 PUFAs have been similarly replicated in two other murine SLE models, BXSB/MpJ and MRL-1pr/1pr, as evidenced by decreased proteinuria and glomerular injury as well as increased lifespan [14], [21], [22]. Effects of fish oil in MRL-1pr/1pr mice were linked to altered eicosanoid metabolism as well as decreased plasma IL-6, IL-10, IL-12 and TNF-α [23], [24], [25].…”
Section: Introductionmentioning
confidence: 78%
“…35,36 However, researchers of another study reported that the survival of mice (MRL/I) was not affected by polyunsaturated fatty acid deficiency. 37 In studies that do show positive results, limiting essential fatty acids may be beneficial because less are then available for the synthesis of specific prostaglandins responsible for inflammation.…”
Section: High Fat (Especially Saturated Fat and Omega-6 Polyunsaturatmentioning
confidence: 99%